Possibility of saliva use in detecting anti herpes simplex virus IgM antibodies - Pavlica Dušan (Serbian Medical Society - Dental Section, Belgrade, 2002)
In this study we investigated the possibility of saliva use instead of sera for detecting anti HSV IgM antibodies. Three groups of patients were included in this study. The first two consisted of immunocompetent persons with clinically and virologicaly approved primary and reccurent herpetic infection. The third group was comprised of AIDS patients with recurrent infection. Anti HSV-1 IgM antibodies were detected by immunofluorescence assay. In saliva and sera samples obtained from persons with primary and recurrent HSV infection, findings of specific IgM antibodies correlated with the dynamic of their synthesis in infection generally. But in the third group, which consisted of AIDS patients, in a few cases there were positive anti HSV IgM concentration, both in sera and saliva samples.